Islamic pedagogical transformation in the digital age: A systematic review on the integration of artificial intelligence in Islamic education - Maulina Hidayatul Ulya; M. Faqih Irsyad (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to the integration of Artificial Intelligence (AI) in Islamic Religious Education (IRE) amid rapid digital transformation. Employing a systematic literature review guided by PRISMA protocols, data were retrieved from major indexed databases using targeted keywords and Boolean operators. Following a rigorous two-phase screening and predefined inclusion criteria, selected studies underwent thematic-interpretive synthesis to map pedagogical shifts. The findings reveal three critical dimensions. First, AI transitions teachers from knowledge transmitters to facilitators of adaptive, personalized learning while automating administrative burdens. Second, pedagogical deconstruction highlights the irreplaceable role of teachers as moral exemplars (uswah hasanah) and critical thinking guides, prioritizing spiritual and humanistic development over mere data transfer. Third, while AI enhances efficiency, accessibility, and student engagement, it simultaneously poses profound challenges, including data privacy risks, algorithmic bias, eroded traditional spiritual interactions (talaqqi), and the widening digital divide. Ultimately, successful AI integration requires balancing technological innovation with Islamic ethical principles, advocating for enhanced educator digital literacy and equitable policies to foster a progressive, spiritually grounded educational ecosystem.